Laboratory evaluation of susceptibility of natural subpopulations of Aedes aegypti larvae to temephos - Biber, Priscila Ariadna (2006)
Aedes aegypti showed the ability to develop resistance to different insecticides, including temephos, the most widely used larvicide. The objectives of this work were to 1) determine the resistance value of 4 natural subpopulations of Ae. aegypti, identified by their different haplotypes, to the insecticide temephos "Abate 1G (1%)"; 2) determine the lethal concentration (LC)50 and LC90 values by using the Rockefeller strain as control; and 3) estimate the resistance ratios. Mosquito samples were collected in Catamarca, Córdoba, and Posadas (Argentina) and in Yacuiba (Bolivia). Six insecticide concentrations were tested. The Rockefeller strain and the Posadas sample showed susceptibility to the diagnostic concentration (0.012 mg/liter), whereas the mortality in Catamarca was 87%. In the Yacuiba and Córdoba collections, mortality was 74% and 75%, respectively, indicating resistance. These results were coincident with those of the Probit analysis from which the highest resistance ratios were estimated for the last 2 subpopulations (5.2 and 4.9, respectively). Before this study, no information was available about the existence of resistance in natural populations of Ae. aegypti in the studied area.